Production of a large area diffuse arc plasma with multiple cathode - 王城 崔海超 李皖皖 廖梦然 夏维珞 夏维东 (Chinese physics B, 2017)
An arc channel at atmospheric pressure tends to shrink generally. In this paper, a non-transferred DC arc plasma device with multiple cathode is introduced to produce a large area arc plasma at atmospheric pressure. This device is comprised of a 42-mm diameter tubular chamber, multiple cathode which is radially inserted into the chamber, and a tungsten anode with a nozzle in its center. In argon/helium atmosphere, a large area and circumferential homogenous diffuse arc plasma, which fills the entire cross section surrounded by the cathode tips, is observed. Results show that the uniformity and stability of diffuse arc plasma are strongly related to the plasma forming gas. Based on these experimental results, an explanation to the arc diffusion is suggested. Moreover, the electron excitation temperature and electron density measured in diffuse helium plasma are much lower than those of constricted arc column, which indicates the diffuse helium plasma probably deviates from the local thermodynamic equilibrium state. Unlike the common non-transferred arc plasma devices, this device can provide a condition for axial-fed feedstock particles. The plasma device is attempted to spheroidize alumina powders by using the central axis to send the powder. Results show that the powder produced is usually a typical hollow sphere.